A Systematic Literature Review on Strategies and Challenges in Instilling the Values of Religious Moderation at the Junior High School Level - Nazaruddin Iqbal Al Hamiid; Madjid, Abd. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study examines the strategies and challenges involved in instilling the values of religious moderation at the junior high school level through a systematic literature review of 20 selected articles published between 2020 and 2024, employing the Context, Input, Process, and Product (CIPP) model as an analytical framework. Religious moderation in Indonesia plays a crucial role in maintaining social harmony and diversity, particularly amid the growing threats of radicalism and intolerance. Core values such as integrity, solidarity, and tolerance are integrated into the Islamic Religious Education curriculum and reinforced through extracurricular activities and interschool collaboration. Implementation is carried out comprehensively by engaging the entire school ecosystem to foster students’ character development, emphasizing tolerance and love for the nation. However, several challenges persist, including internal resistance, limited evaluation mechanisms, and the influence of broader socio-political dynamics. To address these challenges, the literature highlights solutions such as continuous teacher training, strengthening evaluation systems, collaboration with external stakeholders, and the strategic use of digital media to disseminate messages of tolerance. The findings underscore that the systematic and sustainable cultivation of religious moderation values is essential for developing an inclusive and nationalistic young generation capable of safeguarding national unity within Indonesia’s pluralistic social context. Abstrak: Penelitian ini menelaah strategi dan tantangan dalam menanamkan nilai-nilai moderasi beragama di tingkat sekolah menengah pertama melalui tinjauan pustaka sistematis terhadap 20 artikel terpilih yang diterbitkan antara tahun 2020 hingga 2024, dengan menggunakan model Context, Input, Process, and Product (CIPP) sebagai kerangka analisis. Moderasi beragama di Indonesia memegang peran penting dalam menjaga harmoni sosial dan keberagaman, khususnya di tengah meningkatnya ancaman radikalisme dan intoleransi. Nilai-nilai inti seperti integritas, solidaritas, dan toleransi diintegrasikan ke dalam kurikulum Pendidikan Agama Islam dan diperkuat melalui kegiatan ekstrakurikuler serta kolaborasi antar sekolah. Implementasi dilakukan secara komprehensif dengan melibatkan seluruh ekosistem sekolah untuk membentuk karakter siswa yang menekankan sikap toleran dan cinta tanah air. Namun, sejumlah tantangan tetap ada, termasuk resistensi internal, mekanisme evaluasi yang terbatas, dan pengaruh dinamika sosial-politik yang lebih luas. Untuk mengatasi tantangan tersebut, literatur menyoroti solusi seperti pelatihan guru secara berkelanjutan, penguatan sistem evaluasi, kolaborasi dengan pemangku kepentingan eksternal, serta pemanfaatan media digital secara strategis untuk menyebarkan pesan toleransi. Temuan penelitian menekankan bahwa penanaman nilai-nilai moderasi beragama secara sistematis dan berkelanjutan sangat penting untuk membentuk generasi muda yang inklusif dan nasionalis, yang mampu menjaga persatuan bangsa di tengah konteks sosial Indonesia yang pluralistik.